A cross-sectional examination of the 24-hour movement behaviours in Canadian youth with physical and sensory disabilities. Issue 1 (January 2021) - Arbour-Nicitopoulos, Kelly P.; Bassett-Gunter, Rebecca L.; Leo, Jennifer; Sharma, Ritu; Olds, Timothy; Latimer-Cheung, Amy E.; Martin Ginis, Kathleen A.
Abstract: Background: Canada's 24-Hour Movement Guidelines for Children and Youth provide daily recommendations for physical activity (PA), screen time, and sleep for optimal health. The appropriateness of such guidelines for youth with disabilities remains unknown. Objective: To cross-sectionally examine the 24-h movement behaviours and guideline adherence in youth (ages 12–21 years) with physical and sensory disabilities. Methods: 54 youth with physical and sensory disabilities completed two, 24-h recalls to assess PA, sedentary behaviour, and sleep. Descriptive statistics were used to analyze behavioural patterns and guideline adherence. Gender and age differences were tested using analyses of variance and logistic regressions. Results: 55.5%, 13.0%, and 53.7% of the sample met the individual guidelines for PA, sedentary behaviour, and sleep, respectively. 3.7% of the sample met all three movement guidelines. No significant gender or age differences in guideline achievement were found. Over a 24-h period, youth spent 77 (59) minutes engaging in moderate to vigorous PA, 252 (120) minutes engaging in sedentary activity, and 546 (90) minutes sleeping. Boys reported significantly more time (adjusted M difference = 11 min) playing passive video games than girls. Conclusion: Overall, our sample of youth with physical and sensory disabilities falls far short of meeting the Canadian 24-Hour Movement Guidelines for Children and Youth. The low proportion of youths' time spent engaging in sport and active play is concerning, highlighting the importance of creating access to these types of PA experiences for this population. Future population-based research is needed among children and youth with all types of disabilities to build an evidence-base of their movement behaviours.